Advances in human factors, business management and leadership : proceedings of the AHFE 2017 International Conferences on Human Factors in Business Management and Leadership, and Business Management and Society, July 17-21, 2017, the Westin Bonaventure Hotel, Los angeles, California, USA /: proceedings of the AHFE 2017 International Conferences on Human Factors in Business Management and Leadership, and Business Management and Society, July 17-21, 2017, the Westin Bonaventure Hotel, Los angeles, California, USA. ([2018]) - Unknown
No abstract available